1997
DOI: 10.1046/j.1365-2621.1997.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Identity and overall acceptance of two types of sour rye bread

Abstract: Response surface methodology was employed to study the influence of four recipe variables (wheat: rye flour ratio, bread acidity, ash content of rye flour and sodium chloride content) on the identity and overall acceptance of two rye bread types (soft and crisp rye bread). The subjects (n ϭ 79) rated attribute intensities, the extent to which the salient sensory properties and the overall sample corresponded to their expectations of rye bread, and the overall acceptance (pleasantness and purchase intentions). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 14 publications
(14 reference statements)
2
15
0
1
Order By: Relevance
“…kibbled rye) as compared to croissant and sample BR6 that were produced from refined wheat flour (Table 1). Previous studies have established that breads produced with whole grains possess typical grainy odour, sour flavour, and coarse texture (Heinio et al, 1997. It is well known, that bran fractions of whole grains contain a rich source of phenolic compounds which impart sour, bitter, grainy, cereal and oat-like flavour characteristics of whole cereal based products (Dimberg, Molteberg, Solheim, & Frolich, 1996;Heinio, 2003;Molteberg, Magnus, Bjorge, & Nilsson, 1996).…”
Section: Descriptive Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…kibbled rye) as compared to croissant and sample BR6 that were produced from refined wheat flour (Table 1). Previous studies have established that breads produced with whole grains possess typical grainy odour, sour flavour, and coarse texture (Heinio et al, 1997. It is well known, that bran fractions of whole grains contain a rich source of phenolic compounds which impart sour, bitter, grainy, cereal and oat-like flavour characteristics of whole cereal based products (Dimberg, Molteberg, Solheim, & Frolich, 1996;Heinio, 2003;Molteberg, Magnus, Bjorge, & Nilsson, 1996).…”
Section: Descriptive Analysismentioning
confidence: 99%
“…doi:10.1016/j.foodres.2008.08.002 perceptions for different varieties of bread. On the contrary, several studies have been carried out to investigate the influence of ingredients, processing, and variety on the sensory quality and consumer perceptions of bread (Heinio, Liukkonen, Katina, Myllymaki, & Poutanen, 2003;Heinio, Urala, Vainionpaa, Poutanen, & Tuorila, 1997;Hersleth, Berggren, Westad, & Martens, 2005;Kihberg, Johansson, Kohler, & Risvik, 2004;Lotong, Chambers, & Chambers, 1999;Shogren, Mohamed, & Carriere, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the north of Europe, for example, where bread tends to contain a high proportion of crumb with one or more cereals, sourdough use is widespread and the product tends to be used for sandwiches or toast, a gradual salt‐reduction strategy similar to that applied in the UK may be suitable. Indeed, it has been shown that the perceived saltiness of bread increases with acidity 130 and that, in Finland, the salt content of sour rye bread is not a key factor in terms of consumer acceptance 131 …”
Section: The Commercial Viewpointmentioning
confidence: 99%
“…Observations of ingredient composition (Table 1) indicate that croissant, brioche, rye bread, butter cake and short biscuit contained either a high level of fat and/or sugar. It is widely known that changing the food matrix composition and manufacturing conditions of complex food systems such as breads, cakes and biscuits will influence the perception of the sensory characteristics (Abdallah, Chabert, Le Roux, & Louis-Sylvestre, 1998;Baardseth, Naes, & Vogt, 1995;Brauss, Balders, Linforth, Avison, & Taylor, 1999;Cardello & Schutz, 2003;Hebeda & Zobel, 1996;Heinio, Urala, Vainionpaa, Poutanen, & Tuorila, 1997). Abdallah et al (1998) showed that the level of fat and sugar in biscuits and cakes enhanced flavour intensity, which in turn was very closely related to pleasantness perceptions.…”
Section: Consumer Freshness Evaluationsmentioning
confidence: 99%